THU0128 Characteristics of Patients with Rheumatoid Arthritis in Kuwait: Results from the Krrd Registry. (9th June 2015) - Al-Herz, A.A.; Saleh, K.; Al-Awadhi, A.; Al-Kandari, W.; Hasan, E.; Abutiban, F.; Alenizi, A.; Ghanem, A.; Hussain, M.; Ali, Y.; Khadrawy, A.; Fazal, A.; et al.
Abstract : Objectives: To describe characteristics of patients with RA in Kuwait focusing on demographic and serological features and common comorbidities and compare them with other RA populations. Methods: Adult patients with RA enrolled in The Kuwait Registry for Rheumatic Diseases (KRRD) from February 2013 through May 2014 were studied. They were recruited from the rheumatology departments of four major hospitals in Kuwait. Demographic, clinical and laboratory data were collected via rheumatologists and trained nurses through patient interviews and from medical records. A comparison with Kuwaiti general population and other RA populations were made. Statistical tests were applied where appropriate. Results: 556 patients were enrolled with a mean age of 49+12 years (range, 17-74) and disease duration of 3.1+5 years. RA diagnosis was made at an age of 46+13 years (14-71). 76.8% were female. 12.9% had a family history of an inflammatory autoimmune rheumatic disease. Only 3.6% had rheumatoid nodules. Rheumatoid factor (RF) and anti-cyclic citrullinated peptide (ACA) were detected in 73% and 58%, respectively. Both were positive in 47.7% (r=0.287, p=0.001). Both ACA and a combination of RF and ACA were more prevalent in females (p=0.034, 0.001, respectively). About one third of male patients were smokers versus 3.4% of females with no significant correlation between smoking and RF or ACA. Anti-nuclear antibody test was positive in 12%. Diabetes mellitus (DM) and hypertension were the commonest co- morbidities, being detected in a total of 36.2%, hyperlipidemia in 7.4% and coronary artery disease (CAD) in 2.7%. Only 3 cases of cancer were reported, all of them were solid cancers. Conclusions: RA in Kuwait manifests at a younger age and with a higher prevalence of positive family history than in other RA populations. CAD was less frequent which may be related to lower rates of hypertension, hyperlipidemia and smoking in our registry. A higher prevalence of DM, however, reflects a high background prevalence of DM in Kuwait. Disclosure of Interest: None declared